UN NEOMARTIRE ORTODOSSO NEL TEATRO GESUITICO: Il caso interconfessionale di Markos Kyriakopoulos = AN ORTHODOX NEOMARTIER IN THE JESUITIC THEATER: The interfaith case of Markos Kyriakopoulos . - Bruno-Chomin, Giuseppe (Rivista di storia del cristianesimo, 2021)
The Ottoman Empire of the early modern period was inhabited by people from across Europe and the Mediterranean. Many Christians embraced Islam to facilitate their integration into Ottoman society. Yet some regretted their apostasy and, as an act of contrition, sacrificed their lives at the hands of Ottoman officials. These individuals became known as "neomartyrs", and their hagiographies circulated among Christians in support of their common faith. This essay considers the Orthodox neomartyr Markos Kyriakopoulos whose death, witnessed and documented by Jesuit missionaries, transcended geographical and cultural boundaries. His conversion experience was incorporated into Catholic historiography and, during the late Counter-Reformation, was adapted by several Jesuit colleges for their didactic theater. Jesuit dramatists recognized the interdenominational value of Markos’ story, which they appropriated and modified, during a period of sociocultural and interreligious tension.